'Legislative frame representation': towards an empirical account of the deliberative systems approach. Issue 3 (2nd July 2016) - Beste, Simon
ABSTRACT: The systemic approach to deliberative democracy is an empirically underexplored topic. Since 'classic' micro indicators for deliberation are at loggerheads with the idea of distributed deliberation, appropriate assessment techniques for large-scale public deliberation are few and far between. This paper aims at exploring a novel pathway into the empirical translations of the deliberative systems approach, using discourse content and the representation of policy frames in the legislature. I argue that legislative frame representation (LFR) is a crucial indicator for the level of sub-systemic deliberative uptake and policy responsiveness. Next to the necessary theoretical and methodological work, the results of an explorative case study for the immigration discourse in the US and Canada are presented. The results indicate that there are considerable differences in the systems' capacities to take up discourses from civil society and that LFR can be an important tool to explore deliberative systems empirically.